Impact of the varieties obonuco andina and San Isidro in the department of Nariño, Colombia - Cadena Pastrana, Alvaro Mauricio (2022)
This research estimated the adoption and impact of the Obonuco Andean and Obonuco San Isidro pea varieties in the department of Nariño, during the period 2017 - 2019. Semi-structured interviews, life stories and focus groups were conducted with key actors; economic estimation of the additional benefit for the producers due to the use of the technology and the estimation of socio-environmental impacts with the Ambitec-Agro method. Among the factors for the adoption of these varieties is their high productivity and performance compared to other materials available in the region, the opening of markets to green grain varieties and low oxidation; As indirect factors, the generation of rural employment is observed due to the diversification of productive roles and the involvement of women and their specialization in tutoring activities. It is estimated, during the evaluated period, an average annual additional benefit for producers, due to the use of technology, of 49,079,940,000 COP, from 12,900 hectares planted per year. Regarding the socio-environmental impacts, the following stand out: improvement in gender and age equity, job creation and qualification, income generation, increase in social capital and improvement in food security. Negative impacts are estimated: greater use of agricultural inputs; loss in air, soil and water quality; decline in biodiversity conservation; that infer the need to work on research processes aimed at improving the sustainability and resilience of the productive system with its natural environment.